Adsorption/desorption performance of Pb2+ and Cd2+ with super adsorption capacity of PASP/CMS hydrogel - Hao Wang (IWA Publishing, 2021)
Super-absorbent polyaspartic acid/carboxymethyl Salix psammophila powder (PASP/CMS) hydrogel was prepared by aqueous solution polymerization. PASP/CMS hydrogel was characterized by Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The results showed that PASP/CMS hydrogel is prepared by graft copolymerization of the -COOH of polyaspartic acid (PASP) and the -CH2OH of CMS. The surface of the hydrogel became dense from loose porosity, and Pb2+ and Cd2+ were adsorbed onto the surface of hydrogel. The crystallinity of CMS was destroyed by the addition of PASP. The initial concentration of Pb2+ and Cd2+, pH, adsorption time and adsorption temperature on the adsorption effect were studied through experiments. Results showed that hydrogel has a good removal effect on Pb(II) and Cd(II) ions. Pseudo-second-order kinetics and Langmuir isotherm models are represented in the process, which are spontaneous, exothermic and decreased in randomness, and it is a single layer chemical adsorption. At the same time, the effect of desorption experimental parameters (HNO3 initial concentration, desorption time, and desorption temperature) on the experiment was studied and optimized. Highlights With the addition of PASP, the structure of CMC was destroyed and PASP/CMS hydrogel was formed.; The adsorption of lead and chromium ions by hydrogels accords with the Langmuir isothermal model and quasi-second-order kinetic model.; The adsorption is a monolayer chemical adsorption.; The adsorption is a spontaneous exothermic process.; The heavy metal ions were adsorbed on the surface of the hydrogel.;